1993
DOI: 10.1007/bf00190954
|View full text |Cite
|
Sign up to set email alerts
|

Internal waves generated by the turbulent wake of a sphere

Abstract: Internal waves generated by the turbulent wake of a sphere travelling horizontally through a linearly stratified fluid were studied using shadowgraph and particle-streak photography. The Reynolds and internal Froude number ranges considered were 2,000 < Re < 12,900 and 2.0 < Fi < 28.0, respectively. Two quite distinct flow regimes based on the structure of the turbulent wake were identified. In one, the wake is characterized by "large-scale coherent structures". In the other, the wake, as viewed on a side-view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Further comparisons to lee wave models are presented in § 3.4.3. Finally, the transition between the lee wave and the turbulent wake generation regimes agrees with the Fr ≈ 2 location noted by Chomaz et al (1991, Lin et al (1993) and Robey (1997). The large run-to-run variation in PE A at Fr = 2 and 5 (and to some degree at Fr = 1) is due to the presence of wake turbulence-generated IWs, as further discussed in the following section.…”
Section: Variation Of Iw Pe With Froude Numbersupporting
confidence: 63%
See 2 more Smart Citations
“…Further comparisons to lee wave models are presented in § 3.4.3. Finally, the transition between the lee wave and the turbulent wake generation regimes agrees with the Fr ≈ 2 location noted by Chomaz et al (1991, Lin et al (1993) and Robey (1997). The large run-to-run variation in PE A at Fr = 2 and 5 (and to some degree at Fr = 1) is due to the presence of wake turbulence-generated IWs, as further discussed in the following section.…”
Section: Variation Of Iw Pe With Froude Numbersupporting
confidence: 63%
“…For a towed sphere, the degree of mixing is substantially less, so that the global collapse of the wake does not contribute substantially to the generation of IWs, as discussed by Bonneton et al (1993). The transition between the lee wave IW regime and the turbulent-wake-generated random wave regime has been found to occur at Fr = 2 by Chomaz et al (1991, Lin, Boyer & Fernando (1993) and Robey (1997). However, the transition between regimes is not precise, as there is a range of Fr where both mechanisms can generate IWs.…”
Section: Stratified Wakesmentioning
confidence: 94%
See 1 more Smart Citation
“…A stratified towed-sphere wake is characterized by its Reynolds number Re ≡ UD/ν and Froude number Fr ≡ 2U/(ND), where U, D, ν and N are the tow speed, sphere diameter, viscosity and buoyancy frequency, respectively. Pioneering and recent experimental studies (Gilreath & Brandt 1985;Hopfinger et al 1991;Bonneton, Chomaz & Hopfinger 1993;Lin, Boyer & Fernando 1993;Robey 1997;Meunier 2012;Brandt & Rottier 2015) revealed at least two types of IWs generated by stratified wakes: the lee waves behind the sphere (or cylinder) which dominates at Fr < 4, and the quasirandom waves emitted by the turbulence in the wake which dominates at Fr 4, the latter wave type being the focus of the present study. Källén (1987) formulated the linear theory for wave generation by the spatially varying mean-flow structure of the wake.…”
Section: Internal Waves Emitted By Localized Stratified Turbulencementioning
confidence: 82%
“…When these intrusions, i.e., coherent structures, are fairly periodic, they generate an asymptotic wave field which has been described by both Gilreath and Brandt 5 and Voisin. 6 Furthermore, Lin et al 7 and Sysoeva and Chashechkin 8 have concluded from measurements that the coherent structures of the wake represent the basic source of internal waves in the wake without explaining clearly the wave generation mechanism.…”
Section: Introductionmentioning
confidence: 99%